Acceleration of ventricular response to atrial flutter after intravenous adenosine. Issue 3 (March 1993) - Rankin, A C; Rae, A P; Houston, A
Abstract : Adenosine may be of therapeutic and diagnostic value in the emergency management of arrhythmias. It causes transient atrioventricular nodal block and thus ends paroxysmal supraventricular tachycardias that involve the atrioventricular node. Also, it may uncover underlying atrial arrhythmias by slowing the ventricular response. Its duration of action is brief and serious adverse effects have not been reported. A 12 year old patient with atrial flutter is presented, in whom intravenous adenosine was followed by acceleration of the heart rate to a potentially dangerous arrhythmia.